Perfluorooctane sulfonic acid (PFOS) inhibits vessel formation in a human 3D co-culture angiogenesis model (NCFs/HUVECs). (15th January 2022) - Forsthuber, Martin; Widhalm, Raimund; Granitzer, Sebastian; Kaiser, Andreas Marius; Moshammer, Hanns; Hengstschläger, Markus; Dolznig, Helmut; Gundacker, Claudia
Abstract: Perfluorooctane sulfonic acid (PFOS) is a ubiquitous environmental pollutant. In humans, PFOS exposure has been associated with a number of adverse health outcomes, including reduced birth weight. Whether PFOS is capable of affecting angiogenesis and thus possibly fetal development is unknown. Therefore, we investigated 1) the metabolic activity of PFOS-exposed endothelial cells (human umbilical vein endothelial cells, HUVECs), fibroblasts (normal colon fibroblasts, NCFs), and epithelial cells (human colorectal carcinoma cells, HCT116), 2) PFOS-specific inhibition of vascular endothelial growth factor receptor (VEGFR)2 stimulation in KDR/NFAT-RE HEK293 cells, and 3) the antiangiogenic potential of PFOS in a 3D in vitro angiogenesis model of HUVECs and NCFs. In terms of metabolic activity, endothelial cells (HUVECs) were much more sensitive to PFOS than fibroblasts (NCFs) or epithelial cells (HCT116). VEGFR2 signaling in KDR/NFAT-RE HEK293 cells decreased with increasing PFOS concentrations. In co-culture (angiogenesis assay), PFOS treatment resulted in a dose-dependent reduction in tip and branch formation, tip length (μm), and total structural area (μm 2 ) with stable metabolic activity of HUVECs up to high concentrations. We conclude that PFOS possesses antiangiogenic properties. Inhibition of VEGFR2 signaling indicates a possible mechanism of action that can be linked to an existing Adverse Outcome Pathway (AOP43) containing the AO reduced birth weight. Further studies are needed to confirm PFOS-specific adverse effects on angiogenesis, placental perfusion, and fetal growth. Graphical abstract: Image 1 Highlights: Endothelial cells are specifically sensitive to PFOS. PFOS inhibits VEGFR2 signaling in a dose-dependent manner. PFOS shows antiangiogenic properties in a 3D co-culture angiogenesis model.